28. QUALITY OF REGULAR HEALTHCARE EXAMINATION IN MILITARY HOSPITAL 175 IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to evaluate the quality of service for periodic health check-ups for Viettel employees at Military Hospital 175 in 2022.Research methods: This cross-sectional study (quantitative method) was conducted within 3 months (April to July 2022) at Military Hospital 175. Quantitative data was collected by self-administered interview for 508 Viettel employees who participated to periodic health check-ups at Military Hospital 175. Data was analyzed using SPSS ver 25.0.Results: Quality service is assessed at a good level with an average score of 3.83 points with a rate of good or higher evaluation of 80.3%. All 5 aspects have average service quality over 3.57 points, of which 2 aspects trust (3.92 points with 86% rating from good or higher) and tangible means (3.97 points with 88.8% of evaluations from good or higher) achieves a higher rate of 3 response aspects (3.50 points with 74.8% evaluations from good or higher), guaranteed (3.85 points with 80.5% evaluations good or better) and empathy (3.85 points with 81.3% rating good or higher).Conclusion: Military Hospital 175 should develop policies to improve human resources with more appropriate remuneration and preferential policies. At the same time, the hospital needs to strengthen communication to promote periodic health check-ups as well as the hospital brand.
Keywords: Regular health checkup, quality of service, Military Hospital 175.